Hudební věda : = Musicology = Musikwissenschaft (1964)
The journal's aim is to publish scholarly articles, reviews, conference/symposium reports and documents related to musical culture, with an emphasis on specific Czech aspects of current pursuits in musicology and music theory. (Verlag)